The Contours of Russia in the Works of Jurgis Baltrušaitis: From Poetry to Diplomacy - Снежко, Юлия (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]In this article, some artistic features of the conception of Russia belonging to the poet and diplomat Jurgis Baltrušaitis are analyzed. The material of research are the poems of his that the author had devoted to Russia and his diplomatic letters, which are stored in the Central State Lithuanian Archive and that earlier were not analyzed from this point of view. The subject of the article is of interest because still from one aspect or another question concerning the place of Russia and Lithuania in Baltrušaitis’ life is put forward. Not surprisingly, this is influenced by the unique circumstances surrounding Baltrušaitis’s life – his belonging to both cultures, Lithuanian and Russian. The comparison of the theme of Russia in “remote” in regard of each other genres reveals that they share something in common. It is shown that the lyrical subject in the poems and letters of Baltrušaitis experiences a special lyrical afflatus toward the growing power of Russia (or the Russian nation) and its special mission, which correlate with the space of the Empire. The author of this article demonstrates that the treatment of the theme of Russia in poetry touches the sublime Russian imperial tradition. The reverberation of the imperial sublime is also to be found in his diplomatic letters. However, if, in the analyzed poems, Baltrušaitis felt being part of the Russian imperial culture, in his diplomatic letters, Russia is perceived by the author from the side of the other – the Lithuanian culture – and the remaining afflatus is thus mixed with a constant sense of danger emanating from Russia and anxiety about the fate of the young Lithuanian state. Also, it can be stated that in general, his philosophically-hermetic poetry, the “revolutionary” poems and diplomatic letters devoted to Russia, share a common rhetoric of inner and outer space, inner and outer power, size and motion.Rusijos kontūrai Jurgio Baltrušaičio kūryboje: nuo poezijos prie diplomatijosŠiame straipsnyje analizuojami kai kurie poeto ir diplomato J. Baltrušaičio meniniai Rusijos suvokimo ypatumai. Tyrimo medžiaga – anksčiau šiuo aspektu netyrinėti jo diplomatiniai laiškai, saugomi LCVA, bei eilėraščiai, skirti Rusijai. Tema yra aktuali tuo, kad iki šiol vienu ar kitu aspektu vis keliamas klausimas apie Rusijos ir Lietuvos vietą Baltrušaičio gyvenime, kas yra nulemta Baltrušaičio ypatingos situacijos, jo priklausymo abiems, lietuviškajai ir rusiškajai kultūrai. Rusijos temos gretinimas visiškai skirtinguose žanruose atskleidžia jų sąlyčio tašką. Straipsnyje yra parodoma, kad lyrinio bei laiškų subjekto laikysenai Rusijos atžvilgiu būdingas ypatingas „lyrinis pakylėtumas“ prieš Rusijos ypatingą misiją, jos (ar rusų tautos) augančią jėgą, koreliuojančia su imperijos erdve. Straipsnyje teigiama, kad analizuojami eilėraščiai įsipaišo į rusų imperinio pakylėtumo tradiciją, kurios atgarsių yra ir jo diplomatiniuose laiškuose. Tačiau jei analizuojamuose eilėraščiuose Baltrušaitis jautėsi esąs rusų imperinės kultūros dalimi, diplomatiniuose laiškuose Rusija suvokiama iš kitos, lietuviškos, kultūros pusės, o išlikęs „pakylėtumas“ persipina su nuolatiniu kylančiu iš jos grėsmės pojūčiu ir nerimu dėl jaunos lietuviškos valstybės likimo. Apskritai, jo filosofiškai uždarą poeziją, „revoliucinius“ eilėraščius bei diplomatinius laiškus, skirtus Rusijai, jungia erdvės, dydžio, vidinės ir išorinės jėgos, bei judėjimo retorika.
Keywords: Baltrusaitis, Diplomatic Letters, Poetry, Russia, Imperial Sublime